Chemoselective aerobic oxidation of 2-amino-N-benzylanilines into N-(2-aminophenyl)imines via a nitroxide-free copper catalysis. Issue 16 (18th April 2019) - Zhai, Yadong; Rong, Jing; Zhang, Zhicheng; Cao, Xiang; Su, Zhenni; Zhou, Qingfa; Tao, Chuanzhou
Graphical abstract: Highlights: Copper as catalyst, without nitroxyl radicals and ligands. Molecular oxygen as the sole oxidant at room temperature. Gram-scale synthesis. Abstract: Chemoselective oxidative synthesis of N -(2-aminophenyl)imines from 2-amino- N -benzylanilines was accomplished through combined use of O2 (air) and copper salt. This transformation was performed at room temperature, and the mild oxidation was efficient and chemoselective without using nitroxyl radicals and ligands.